Associação entre a percepção da qualidade de vida, percepção do apoio familiar e recidiva de peso em mulheres com mais de 24 meses de cirurgia bariátrica - FERNANDES, Flavia Aline Lages (2023)
Background: The bariatric surgery is indicated to treat clinically severe obesity when conventional treatment does not offer satisfactory results in weight loss and control of associated comorbidities. However, longterm weight recurrence is common to be observed, which can affect patients' perception of quality of life. Studies suggest that social support after bariatric surgery, with emphasis on family support, may be related to the maintenance of results and, thus, promote impact on the perception of quality of life of these patients. Objective: To test the association among perception of quality of life, perception of family support and weight recurrence in women that had the bariatric surgery over more than 24 months. Method: This is a crosssectional, descriptive and analytical study developed with 50 adult women who underwent bariatric surgery (Roux enY gastric bypass or sleeve) at least 24 months ago. Anthropometric data was collected, considering the occurrence of weight recurrence when it reached ≥15% of the lowest weight after surgery and success in losing excess weight when the loss was higher than or equal 50%. The Item Short Form Healthy Survey (SF36) was used as an instrument to evaluate the perception of quality of life, and a questionnaire to evaluate the perception and satisfaction with family support in the postoperative period. Results: Satisfactory weight loss was observed after surgery. However, 46.0% of the sample (n=23) had significant weight recurrence (16.1± 4.5%). Perception and satisfaction with family support after surgery were good. Participants had better perception of quality of life in domains related to physical aspects and worse scores in domains related to emotional aspects (p<0.000). The general emotional component and general physical component of quality of life were directly associated with the perception of family support and with the